Assessing The Influence Of Personalized Learning And Hands-On Science Engagements On Scientific Inquiry Skills Among Early Childhood Care And Primary Education Students - Chinyere, Umeji Ifeoma (Educator Development Journal, 2025)
This study investigates the impact of personalized learning and hands-on science engagements on the development of scientific inquiry skills among early childhood care and primary education students. The study employed a descriptive survey design in Anambra state, encompassing 143 participants with different demographics. A self-structured questionnaire underwent validation and reliability testing. Data collection utilized a survey-based approach through Google Forms, ensuring diverse participant engagement and representing Early childhood care and primary education students. The survey incorporated Likert scales for nuanced feedback. Data analysis included various statistical measures, illustrating response occurrences, percentages, and descriptive statistics. The ANOVA methodology tested hypotheses, revealing significant differences among group means. The results reveal that personalized learning significantly enhances critical thinking, hypothesis formulation, experimental design, and evidence-based conclusions. Concurrently, hands-on science engagements contribute to deepening inquiry skills, enhancing problem-solving abilities, and creating memorable learning experiences. These findings underscore the importance of tailoring educational experiences and incorporating practical activities to foster a holistic development of scientific inquiry skills among young learners. The study contributes to the evolving landscape of educational methodologies and carries implications for educators, policymakers, and researchers seeking to optimize learning environments for Early childhood care and primary education students.